Effects of Ambient Parameters on the Performance of a Direct-Expansion Solar-Assisted Heat Pump with Bare Plate Evaporators for Space Heating - Wenzhu Huang; Jie Ji; Mawufemo Modjinou; Jing Qin (International Journal of Photoenergy)
Research on the direct-expansion solar-assisted heat pump (DX-SAHP) system with bare plate evaporators for space heating is meaningful but insufficient. In this paper, experiments on a DX-SAHP system applying bare plate evaporators for space heating are conducted in the enthalpy difference lab with a solar simulator, with the ambient conditions stable. The independent effects of ambient temperature, solar irradiation, and relative humidity on the system performance are investigated. When ambient temperature changes as 5°C, 10°C, and 15°C, COP increases as 2.12, 2.18, and 2.26. When solar irradiance changes as 0 W m−2, 100 W m−2, 200 W m−2, 300 W m−2, and 500 W m−2, COP of the system changes as 2.07, 2.09, 2.14, 2.26, and 2.36. With ambient temperature of 5°C and solar irradiance of 0 W m−2, when relative humidity is 50%, no frost formed. Whereas with relative humidity of 70% and 90%, frost formed but not seriously frosted after 120 min of operating. Frost did not deteriorate but improved the heating performance of the DX-SAHP system. The change of relative humidity from 70% to 90% improves the evaporating heat exchange rate by 35.0% and increases COP by 16.3%, from 1.78 to 2.07.